To the theory of elastic and viscoelastic seismic waves propagating in the layered Earth stratum - Kendzera, O.V.; Rushchitsky, J.J. (Reports of the National Academy of Sciences of Ukraine, 2018)
The direct method of mechanics is utilized in studying the passing and reflecting of an SH-wave while it propagates through the finite number of ground layers with differing thicknesses and rheological properties. The mechanical properties of the ground layers are described by the Hookean and standard rheological models. The explicit formulas for the evaluation of the wave number and the attenuation of a harmonic SH-wave are obtained. The wave attenuation is studied by two variants — by th e spatial coordinate and in time. The obtained form ulas can be treated as some continuation of classical works of Prof. Savarensky (Russia) in the area of elastic seismic waves and Prof. Stepanishen (USA) in the area of viscoelastic seismic waves.